The Effect of Radial Shock Wave Therapy and Laser Therapy on Pain in Myalgia Pain Low Back at EMC Hospital, Cikarang in 2022 - Isidorus Jehaman; Rocky Arthur Agustinus Pontoan; Timbul Siahaan; Redi Tantangan; Fitri Ramadani Harahap (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
Low Back Pain (LBP) is a leading cause of disability worldwide, which places a significant economic burden on the healthcare system. Nonspecific low back pain Low back pain (LBP) is defined as low back pain that is not caused by a recognized and recognized specific pathology. Low back pain does not cause death, but causes individuals who experience it to become unproductive so that it will cause a very large economic burden for individuals, families, communities, and governments. Promising physiotherapy measures for the treatment of LBP myalgia are extracorporeal shock wave therapy and laser. The purpose of this study was to determine the effect of radial shock wave therapy and laser therapy on pain in low back pain myalgia patients at EMC Hospital Cikarang in 2022. This research method was experimental with a quasi-experimental approach, namely research by conducting experiments to determine the symptoms or effects that arise. as a result of a certain treatment or experiment with a one group pretest posttest design, with the aim of knowing the effect of radial shockwave therapy and laser therapy on pain in low back pain myalgia patients at EMC Hospital Cikarang in 2022. The number of samples from this study was 12 people. who is an employee of EMC Cikarang Hospital in 2022 with complaints of LBP myalgia. Respondents will be measured the value of pain using Verval Analogue Scale (VAS) before and after being given radial shockwave therapy and laser therapy. The test used to analyze the data is the Wilcoxon test. The results of data analysis using the Wilcoxon test obtained a significance value (p-value) of 0.001 which is smaller than 0.05 (p<0.05), which means that there is a difference in the value of pain before and after giving radial shock wave therapy and laser therapy to pain in patients. low back pain myalgia. The conclusion is that there is an effect of giving radial shock wave therapy and laser therapy to reducing pain in low back pain myalgia patients at EMC Hospital Cikarang in 2022